Peningkatan Kualitas Pembelajaran Melalui Adopsi Dan Implementasi Teknologi Instruksional - Hasan Basri (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2014)
Lately, many educational institutions have adopted the technology to facilitate teaching and learning both inside and outside the classroom; even the technology has been widely used in distance learning system. However, there are still many educational institutions are not 'familiar' with the instructional technology. The lack of such intimacy, on the one hand, can be expected as a result of uneven technological diffusion. On the other hand, it is likely due to limited funds and human resources in the institution. In addition, the decision makers (decision makerAs) are not so enthusiastic about the technology. In the study of Islam, the use of instructional technology becomes an important solution to achieve maximum learning outcomes; as well as anticipation of the challenges and demands of the times. By doing so, Islamic religious education be superior education based cutting-edge technology. Akhir-akhir ini banyak lembaga pendidikan telah mengadopsi teknologi untuk memudahkan proses belajar mengajar baik di dalam maupun di luar kelas; bahkan teknologi telah digunakan secara luas dalam sistem belajar jarak jauh. Namun, masih banyak juga lembaga pendidikan yang belum ‘akrab’ dengan teknologi instruksional itu. Ketidakakraban tersebut, pada satu sisi, dapat diduga sebagai akibat difusi teknologi yang tidak merata. Pada sisi lain, ada kemungkinan karena keterbatasan biaya dan sumber daya manusia dalam lembaga tersebut. Di samping itu, para pembuat keputusan (decision makers) tidak begitu antusias terhadap teknologi. Dalam pembelajaran agama Islam, pemanfaatan teknologi instruksional menjadi solusi penting untuk mencapai hasil pembelajaran yang maksimal; dan sekaligus sebagai antisipasi terhadap tantangan dan tuntutan zaman. Dengan begitu, pendidikan agama Islam menjadi pendidikan unggulan yang berbasis teknologi mutakhir. Kata Kunci: Kualitas Pembelajaran, Adopsi Teknologi Instruksional